State of knowledge in tiller dynamics - Matthew, Cory; Agnusdei, Monica Graciela; Assuero, Silvia Graciela; Sbrissia, André F.; Scheneiter, Jorge Omar; Silva, Sila C. da (University of Kentucky, 2022)
Persistence of sown pastures is a concern for pastoral production worldwide. Fundamentally, when a pasture does not persist the problem can be expressed in terms of inadequate new tiller production or excessive tiller death. However, the collection of data to build an understanding of sward dynamics at this level is time consuming. Tiller survival diagrams are presented for a range of temperate and tropical grass species including Lolium perenne, Lolium multiflorum, Festuca arundinacea, Festuca pratensis, Phleum pratense, Bromus willdenowii, Cynodon dactylon, Brachiaria brizantha, Panicum maximum, Chloris gayana and Paspalum notatum. It is shown that each grass has a unique perennation strategy and accordingly unique strengths and weaknesses that confer persistence or lack of persistence in different situations. There is also confusion in extension circles about the trade-off between tiller size and tiller density and how to detect a suboptimal tiller density. Grass swards respond to high herbage mass by increase of tiller size and reduction in tiller density, but reduction in tiller density is often mistaken for sward decline. A distinctionmust be made between size/density compensation and sward decline. Increased understanding of sward dynamics at this level should help in the evolution of management practices that improve persistence on a range of grassland types.